Vegetable Grafting: Principles and Practices 2017
DOI: 10.1079/9781780648972.0070
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock breeding: current practices and future technologies.

Abstract: This chapter explores how genetic diversity can be exploited more deeply to create new rootstock cultivars, and describes the current and future breeding strategies applicable to rootstocks. It considers how to combine different sources of genetic variation, for example by overcoming species barriers, and how to select useful rootstocks. The many traits that can be associated with the root system or conferred by a rootstock to the scion are outlined. The impact of the practice of grafting on breeding strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Shoot biomass and grafted success rate of the hybrids have increased as compared to the parents, 1.5 times and approximately 20%, respectively. In previous studies, it was reported that interspeci c hybrids rootstocks performed better than C. maxima and C. moschata rootstocks in terms of root vigor and grafting success (Davis et al 2008;King et al 2010;Thompson et al 2017). However, Edelstein et al (2017) found the same rooting capacity values between interspeci c hybrid rootstocks and their parents in grafted melon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shoot biomass and grafted success rate of the hybrids have increased as compared to the parents, 1.5 times and approximately 20%, respectively. In previous studies, it was reported that interspeci c hybrids rootstocks performed better than C. maxima and C. moschata rootstocks in terms of root vigor and grafting success (Davis et al 2008;King et al 2010;Thompson et al 2017). However, Edelstein et al (2017) found the same rooting capacity values between interspeci c hybrid rootstocks and their parents in grafted melon.…”
Section: Discussionmentioning
confidence: 99%
“…Commercial Cucurbits are most commonly grafted onto interspeci c Cucurbita hybrid (C. maxima × C. moschata) rootstocks (Edelstein et al 2017). These interspeci c hybrids have become a widely accepted paradigm for vigorous rootstocks that improve yield and biotic resistance of Cucurbits (Thompson et al 2017). C. maxima × C. moschata crosses generally give rather poor fruit set and seed yield, and usually produce a sterile hybrid plant (Karaağaç and Balkaya 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, undesired traits, such as reproductive incompatibility [44], poor germination of seeds and the reduction in stem girth of plants may limit the scope of using wild species directly as rootstock. Hence, instead of simply using wild species as a rootstock, the hybrids or derivatives of wild species can be successfully used as rootstocks to obtain desired results [14,45]. Several reports suggest that droughtinduced growth inhibition in tomatoes can be circumvented by grafting [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The selection and development of the line or heterotic F 1 hybrid has been a successful approach for developing rootstocks to address the issues related to using wild species, such as a rootstock that retains beneficial traits in the tomato [14]. The wild species of tomato, including S. pimpinellifolium and S. pennellii and even others, are tolerant to various abiotic stresses, including drought [15].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in root function and architecture have resulted in enhancements for crop production (Hammer et al, 2009 ; Siddiqui et al, 2021 ), and much has been achieved to understand the genetic regulation of root system architecture and development, particularly in Arabidopsis (Motte et al, 2019 ). Breeding for improved root systems is of great interest for grafted vegetable production where elite scion genotypes with favourable aboveground traits are grafted onto rootstocks, especially in the solanaceous crops tomato, pepper and eggplant (Thompson et al, 2017 ). When choosing rootstocks, the foremost interests are the overall yield, resistance against biotic and abiotic stresses and improved resource use efficiency (Martínez-Andújar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%